Functional and structural differences between the prion protein from two alleles prnp(a) and prnp(b) of mouse. - Brown, DR; Iordanova, I; Wong, B; Vénien-Bryan, C; Hafiz, F; Glasssmith, L; Sy, MS; Gambetti, P; Jones, I; Clive, C; Haswell, S (2000)
The prion protein is a glycoprotein expressed by neurones and other cells. In its holo-form it binds copper and exhibits superoxide dismutase activity. Studies in mice have led to the description of two distinct alleles. Differences in these alleles are linked to long and short incubation times following infection with scrapie. We studied recombinant mouse protein corresponding to the products of either allele and two intermediates carrying single amino-acid residue substitutions. The different forms of the prion protein exhibited differences in superoxide dismutase (SOD) activity and conformation. Intermediates with single substitutions were less stable than either allelic product. The findings provide insight into the differences between the two alleles and might have consequences for understanding differences in susceptibility to prion disease.